Age-related neurochemical changes in the rhesus macaque inferior colliculus - Engle, James R.; Gray, Daniel T.; Turner, Heather; Udell, Julia B.; Recanzone, Gregg H. (Frontiers in Aging Neuroscience, 2014)
Age-related hearing loss (ARHL) is marked by audiometric hearing deficits that propagate along the auditory pathway. Neurochemical changes as a function of aging have also been identified in neurons along the auditory pathway in both rodents and carnivores, however, very little is known about how these neurochemicals change in the non-human primate. To examine how these compensatory neurochemical changes relate to normal aging and audiometric sensitivity along the auditory pathway, we collected auditory brainstem responses (ABRs) and brain specimens from seven rhesus monkeys spanning in age from 15 to 35 years old, and examined the relationship between click evoked ABR thresholds and the ABR evoked pure tone average and changes in the number of parvalbumin and NADPH-diaphorase positive cells in the auditory midbrain. We found that the number of parvalbumin positive cells in the central nucleus and the surrounding cortex regions of the inferior colliculus were strongly correlated with advancing age and ABR pure tone average. We also found that the numbers of NADPHd positive cells in these same regions were not associated with normal aging or changes in the ABR thresholds. These findings suggest that the auditory midbrain undergoes an up-regulation of parvalbumin expressing neurons with aging that is related to changes in the processing of frequencies across the audiometric range.